4CPS-072 Comparison of immune checkpoint inhibitors (nivolumab, pembrolizumab, atézolizumab and durvalumab) in the treatment of non-small cell lung cancer: tolerance and financial impact. (24th March 2020) - Badibouidi, F; Dupont, L; Benchaabane, M; Loutski, S
Abstract : Background and importance: Immune checkpoint inhibitors represent a major therapeutic option for the management of non-small cell lung cancer. However, the setback on their use in practice is limited. Aim and objectives: The aim of the study was to compare the real world data for anti-PD-1 and anti-PD-L1 antibodies (nivolumab, pembrolizumab, atézolizumab and durvalumab) in terms of tolerance and financial impact in our hospital. Material and methods: An observational study was conducted over 1 year including patients treated with either nivolumab 240 mg or durvalumab 10 mg/kg every 2 weeks or pembrolizumab 200 mg or atézolizumab 1200 mg every 3 weeks. The comparison criteria were patient profile, tolerance and cost of treatment. Annual drug costs were calculated based on VAT (2.1%). In the case of weight dependent doses (durvalumab), mean weight was 80 kg (total doses per administration, 800 mg). The data were collected from computerised patient records (CliniCom and Chimo). Results: We analysed 53 patients: nivolumab (n=24), pembrolizumab (n=20), durvalumab (n=8) and atézolizumab (n=1). Mean age was 67 years and 79% of patients were men. The firstline treatment was durvalumab for all patients and pembrolizumab for four patients. The mean number of treatment cycles was: nivolumab (n=16), pembrolizumab (n=9.3), durvalumab (n=4.5) and atézolizumab (n=6). Side effects occurred in 64% of patients (79% nivolumab, 45% pembrolizumab and 50% durvalumab). Haemoptysis caused hospitalisation in two patients (pembrolizumab n=1, durvalumab n=1). Reasons for stopping treatment were progression (9% nivolumab, 25% pembrolizumab and 100% atézolizumab) and side effects (14% nivolumab, 15% pembrolizumab and 12.5% durvalumab). The most common side effects were pneumonitis (37% nivolumab and 5% pembrolizumab), metabolism disorders (25% durvalumab, 12.5% nivolumab and 5% pembrolizumab) and diarrhoea (15% pembrolizumab and 8% nivolumab). The annual costs of treatments were €61 871 for atézolizumab, €66 000 for nivolumab, €93 038 for pembrolizumab and €100 450 durvalumab. Conclusion and relevance: Our study showed that the incidence of pneumonitis seemed to be higher with nivolumab and that treatment interruption was more important for pembrolizumab. Nivolumab seemed to be generally better tolerated than the other agents. Nevertheless, for patients with baseline respiratory diseases, pembrolizumab could be considered the preferred option. References and/or acknowledgements: 1. Giuliani J, et al. Anticancer Res 2019;39:3961–3965. No conflict of interest.